2021
DOI: 10.1002/jor.24999
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Staphylococcus aureus stainless steel‐associated infections in orthopedics. A systematic review and meta‐analysis of animal literature

Abstract: Surgical site infection in the presence of orthopedic implants poses significant healthcare and socioeconomic burden. To assess the potential of various prevention strategies against Staphylococcus-induced stainless steel-associated infections, a review of animal evidence was designed. The databases of PubMed, Embase, and CENTRAL were searched until March 10, 2020, for articles including animal models with stainless steel instrumentation and techniques to prevent Staphylococcus infection. We conducted a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The review and meta-analysis performed by Tsikopoulos et al assessed the potential of stainless steel and its modifications to prevent S. aureus infection in animal models [ 34 ]. The analysis showed that passive or active coating of stainless-steel implants reduces MRSA or MSSA infections in various animal models using different antimicrobial substances.…”
Section: Resultsmentioning
confidence: 99%
“…The review and meta-analysis performed by Tsikopoulos et al assessed the potential of stainless steel and its modifications to prevent S. aureus infection in animal models [ 34 ]. The analysis showed that passive or active coating of stainless-steel implants reduces MRSA or MSSA infections in various animal models using different antimicrobial substances.…”
Section: Resultsmentioning
confidence: 99%
“…Using a protective coating may also increase the corrosion resistance of the stainless steel and promote more excellent compatibility with the surrounding human tissues, which is also indispensable 3,10,11 . Organic coatings can be used to enhance the antibacterial response of stainless steel orthopedic implants 12 . Composite coatings of chitosan and silver nanoparticles were applied to coat AISI 304L for orthopedic implants using galvanic deposition, showing improved corrosive protection in a simulated body fluid at 37 o C 13 .…”
Section: Introductionmentioning
confidence: 99%
“…23,27 There are only few systematic reviews and meta-analyses of animal studies of antimicrobial coated implants using various inorganic materials and organic compounds rather than the promising AMPs. 28,29 In this study, a systematic review has been undertaken to find out whether AMP-modified metallic implants showed antibacterial efficacy in in vivo induced infection models and if these AMP-coated implants may have potential in clinical applications. To this end, the different AMPs undergo comparisons, and where relevant, a metaanalysis has been performed to obtain effect size and heterogeneity.…”
Section: Introductionmentioning
confidence: 99%